Are All the Women Still White? : Rethinking Race, Expanding Feminisms - Hobson, Janell, 1973- (Book collections on Project MUSE., 2016)
"Provides a contemporary response to such landmark volumes as All the Women Are White, All the Blacks Are Men, But Some of Us Are Brave and This Bridge Called My Back. More than thirty years have passed since the publication of All the Women Are White, All the Blacks Are Men, But Some of Us Are Brave. Given the growth of women's and gender studies in the last thirty-plus years, this updated and responsive collection expands upon this transformation of consciousness through multiracial feminist perspectives. The contributors here reflect on transnational issues as diverse as intimate partner violence, the prison industrial complex, social media, inclusive pedagogies, transgender identities, and (post) digital futures. This volume provides scholars, activists, and students with critical tools that can help them decenter whiteness and other power structures while repositioning marginalized groups at the center of analysis."--Publisher's description.